In-situ joining of carbon fiber reinforced silicon carbide composite to Ni-based single-crystal superalloy by active unidirectional casting technology - Fu Wang; Lingfeng Qu; Jing Wang; Yingxing Wang; Yazhou Li; Qiang Yang; Yunsong Zhao; Dichen Li; Zhanyi Zheng (Materials & Design, 2023)
Aiming to join large-scale Cf/SiC with a complex joining structure to SC CMSX-6 superalloy, a novel active unidirectional casting technology was developed to in-situ form a joint with satisfactory bonding strength. The integrity of the single crystal (SC), interfacial structure, phase formation, and high-temperature mechanical property were studied. The results demonstrated successful formation of a complete CMSX-6 SC structure with a crystallographic orientation deviation of 13.2° from the (001) direction, joined with Cf/SiC. A gradient reaction interlayer composed of γ/γ΄ matrix, AlN, Cr3C2, and TiMoC2 phases was formed. The maximum tear strength of the joining interface reached 32.9 MPa at 750 °C, approximately 2.5 times larger than the interlaminar bonding strength of Cf/SiC. This satisfactory mechanical property was attributed to the pinning effect resulting from the infiltration of molten CMSX-6 into Cf/SiC and reduced thermal stresses facilitated by the formed gradient bonding interface.